Preparation method and application of tellurium selenium molybdenum sulfide catalyst
By introducing selenium and tellurium into MoS2, the formation of a molybdenum tellurium sulfide catalyst is solved, and the problems of polysulfide solubility and electrode circulation stability in lithium sulfur batteries are significantly improved, thus achieving the energy density and cycle life of lithium sulfur batteries. More efficient electrochemical properties.
Patent Information
- Application Number
- CN202411591673.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
In practical applications, lithium-sulfur batteries face problems such as polysulfide solubility and electrode cycling stability, which limits the actual performance of MoS2 and the overall performance of Li-S batteries.
By dissolving selenium powder, sodium molybdate dihydrate and thiourea in a reduced graphene oxide suspension, a mixed solution was formed, and mixed with a hydrazine hydrate solution of selenium powder to undergo hydrothermal reaction to obtain a molybdenum tellurium selenium sulfide catalyst. The catalyst forms layered nanosheets by annealing, which has infinite solid solution and abundant defects.
The catalyst exhibits higher energy density and longer cycle life in lithium-sulfur batteries, with an initial capacity of 990mAh·g-1, and a capacity retention rate of about 87% after 200 cycles. The preparation method is simple and easy Operation, suitable for industrial production.
Smart Images

Figure CN119455987A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a preparation method of a molybdenum tellurium selenide sulfide catalyst and application thereof. Background Art
[0002] With the rise of the industrial revolution, industrialization and the prosperity of human society, fossil fuels, as the main energy source for human economic development, are facing the crisis of depletion under the continuous growth of global energy demand. On the other hand, the burning of fossil fuels and human activities have caused a series of environmental problems, such as global warming, melting glaciers, and land desertification. Cheap and clean renewable energy is an important way to solve energy problems. Among them, lithium-ion batteries have considerable mass energy density, no memory effect, and high open circuit voltage, making them the most important members of commercial energy storage devices. With the growth of global demand for sustainable energy, lithium-ion batteries, as one of the main energy sources for portable electronic devices and electric vehicles, have become the focus of scientific research. Among them, lithium-sulfur batteries have attracted widespread attention due to their high energy density and low cost, and have become an important candidate for the next generation of battery technology. However, lithium-sulfur batteries face many challenges in practical applications, especially the solubility of polysulfides and the cycling stability of electrodes. In recent years, molybdenum disulfide (MoS2) has been considered as an effective material to solve these problems due to its excellent chemical stability and catalytic performance.
[0003] Although the application of molybdenum disulfide (MoS2) in lithium-sulfur (Li-S) batteries has shown many potential advantages, such as improving the electrochemical performance of the battery, inhibiting the shuttle effect of polysulfides, and enhancing catalytic activity, there are still problems such as insufficient conductivity, interfacial effects, and lack of catalytic activity in practical applications. These problems may limit the actual performance of MoS2 and the overall performance of Li-S batteries. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method of a molybdenum telluride selenide sulfide catalyst and its application. By improving MoS2 to design an electrode material with high capacity, excellent reversibility and good cycle stability, it is of great significance to the application of batteries.
[0005] To achieve the above object, the present invention provides a method for preparing a molybdenum telluride selenide sulfide catalyst, comprising the following steps:
[0006] S1, adding selenium powder to hydrazine hydrate solution to form solution A;
[0007] S2, dissolving sodium molybdate dihydrate and thiourea in the reduced graphene oxide suspension to form a mixed solution B;
[0008] S3, mixing solution A and solution B and stirring to obtain solution C, and placing solution C in an autoclave for hydrothermal reaction;
[0009] S4, washing the product obtained by the hydrothermal reaction with deionized water, and freeze-drying to obtain a black product A;
[0010] S5. Place the tellurium powder at the upwind side of the tubular furnace, and place the product A at the downwind side of the tubular furnace, and perform annealing treatment in an argon-hydrogen atmosphere to obtain a tellurium-selenium-molybdenum sulfide catalyst.
[0011] Preferably, the mixing temperature of selenium powder and hydrazine hydrate in S1 is 50-100° C., the purity of selenium powder is >99.99%, the particle size is <75 μm, and the hydrazine hydrate is analytical grade.
[0012] Preferably, the purity of sodium molybdate dihydrate in S2 is >99.99%, and the concentration of reduced graphene oxide in solution B is 3-20 mg / mL.
[0013] Preferably, in S3, the stirring temperature is 40-80° C., the stirring time is 0.25-3 h, the hydrothermal reaction temperature is 160-250° C., and the hydrothermal reaction time is 10-30 h.
[0014] Preferably, the mass ratio of tellurium powder to product A in S5 is 1:2-0.1, the annealing temperature is 400-800°C, and the time is 1-6h.
[0015] Preferably, the concentrations of selenium powder, sodium molybdate dihydrate and thiourea in solution C are all 2-8 mmol / mL.
[0016] Preferably, the volume percentage content of hydrazine hydrate in solution C is 10-50%.
[0017] Preferably, the mass percentage of the single elements S, Se and Te in the molybdenum tellurium selenide sulfide catalyst is 10-80%.
[0018] The present invention also provides an application of a molybdenum telluride selenide sulfide catalyst, and the molybdenum telluride selenide sulfide catalyst prepared by the above-mentioned preparation method of the molybdenum telluride selenide sulfide catalyst is used as a positive electrode material to prepare a lithium-sulfur battery.
[0019] Therefore, the present invention adopts the above-mentioned preparation method of molybdenum tellurium selenide sulfide catalyst and its application, which has the following beneficial effects:
[0020] (1) The present invention combines chalcogen elements Te, Se, and S with Mo at the same time to form an infinite solid solution chalcogen catalyst. This modification leads to the rearrangement of the electronic structure of Mo, accelerates the redox reaction of polysulfides, increases the binding energy with polysulfides, and reduces its conversion energy barrier. In addition, the introduction of different chalcogen anions forms different interlayer spacings, enhances the intrinsic conductivity, increases the ion diffusion rate, and moves the d-band center upward, thereby reducing the occupancy of electrons in the antibonding orbital and accelerating the conversion of polysulfides. The synthesized catalyst has important practical application value in lithium-sulfur batteries.
[0021] (2) The preparation method of the present invention obtains a molybdenum telluride selenide sulfide catalyst grown on reduced graphene oxide through simple and mild solution treatment and hydrothermal reaction. The catalyst has a large number of defects on the surface, and the defect concentration and the telluride selenide sulfur ratio are controllable. The defect concentration and the telluride selenide sulfur ratio can be controlled by adjusting the reaction time, temperature, the amount of telluride selenide sulfur source and other conditions.
[0022] (3) The molybdenum telluride selenide sulfide catalyst of the present invention, after being prepared into a lithium-sulfur battery, has a higher energy density and a longer cycle life than a lithium-sulfur battery prepared with molybdenum disulfide. Under 1C conditions, the initial capacity is 990 mAh·g -1 , the capacity retention rate after 200 cycles is about 87%, which has better application prospects in lithium-sulfur batteries.
[0023] (4) The preparation method of the molybdenum telluride selenide sulfide catalyst of the present invention is simple and easy to operate, and does not require complicated instruments and equipment. The molybdenum telluride selenide sulfide and molybdenum source are used as synthetic materials, which are low in price compared to catalyst materials containing precious metals and are suitable for industrial production.
[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a scanning electron microscope (SEM) image of a molybdenum telluride selenide sulfide catalyst prepared in Example 1 of a method for preparing a molybdenum telluride selenide sulfide catalyst of the present invention and its application;
[0026] Figure 2 This is a method for preparing a molybdenum telluride selenide sulfide catalyst and its application example 1 of the present invention, and an element distribution diagram of the molybdenum telluride selenide sulfide catalyst prepared under a scanning electron microscope;
[0027] Figure 3 The present invention discloses a method for preparing a molybdenum telluride selenide sulfide catalyst and a constant current charge and discharge curve of a battery using the molybdenum telluride selenide sulfide catalyst prepared in Example 1 and Comparative Examples 1, 2 and 3 as positive electrode materials at a current of 1C. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0029] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0030] The present invention provides a method for preparing a molybdenum telluride selenide sulfide catalyst, comprising the following steps:
[0031] S1. Add selenium powder to hydrazine hydrate solution to form solution A; the mixing temperature of selenium powder and hydrazine hydrate is 50-100° C., the purity of selenium powder is >99.99%, the particle size is <75 μm, and the hydrazine hydrate is analytical grade.
[0032] S2. Dissolving sodium molybdate dihydrate and thiourea in the reduced graphene oxide suspension to form a mixed solution B; the purity of sodium molybdate dihydrate is >99.99%, and the concentration of reduced graphene oxide in solution B is 3-20 mg / mL.
[0033] S3. Solution A and solution B are mixed and stirred at 40-80° C. for 0.25-3 h to obtain solution C. Solution C is placed in an autoclave for hydrothermal reaction at a temperature of 160-250° C. for 10-30 h.
[0034] The concentrations of selenium powder, sodium molybdate dihydrate and thiourea in solution C are all 2-8 mmol / mL, and the volume percentage content of hydrazine hydrate in solution C is 10-50%.
[0035] S4, washing the product obtained by the hydrothermal reaction with deionized water, and freeze-drying to obtain a black product A;
[0036] S5. Place tellurium powder in the upwind of a tube furnace, place product A in the downwind of the tube furnace, the mass ratio of tellurium powder to product A is 1:2-0.1, and perform annealing treatment in an argon hydrogen atmosphere at a temperature of 400-800°C for 1-6 hours to obtain a tellurium selenide molybdenum sulfide catalyst. The tellurium selenide molybdenum sulfide catalyst is a layered nanosheet that grows uniformly on the redox graphene, is infinitely solid-dissolved, and produces rich defects. The ratio of S, Se, and Te in the tellurium selenide molybdenum sulfide catalyst is adjustable and infinitely solid-dissolved, and the mass percentage of a single element is 10-80%.
[0037] Example 1
[0038] A preparation method of a tellurium selenide molybdenum sulfide catalyst comprises the following steps: first, at 70°C, 0.75 mmol of selenium powder is added to 2.5 mL of hydrazine hydrate solution (98%) to form solution A. Then, 0.75 mmol of sodium molybdate dihydrate and 0.75 mmol of thiourea are dissolved in 10 mL of reduced graphene oxide suspension (10 mg / mL) to form a mixed solution B. Solution A and solution B are mixed together and stirred for 15 minutes to obtain solution C, and solution C is transferred to a Teflon autoclave and stored at 200°C for 24 hours. The product obtained by the reaction is washed with deionized water and freeze-dried to obtain a black product A. Finally, a tubular furnace is used for annealing treatment, 3 mmol of tellurium powder is placed in an upwind position, and product A is placed in a downwind position, and annealing treatment is performed at 550°C in an argon-hydrogen environment for 2 hours to obtain a tellurium selenide molybdenum sulfide catalyst.
[0039] Figure 1 As shown in the scanning electron microscope (SEM) image of the molybdenum telluride selenide sulfide catalyst prepared in Example 1, the layered MoSSeTe nanosheets prepared in Example 1 grow uniformly on the redox graphene, with an average size of about 100 nm.
[0040] Figure 2 This is a scanning electron microscope element distribution diagram of the molybdenum telluride selenide sulfide catalyst prepared in Example 1, which shows the uniform distribution of S, Se, Te and Mo elements on the rGO nanosheets, confirming that S, Se and Te were successfully introduced into the molybdenum telluride selenide sulfide catalyst.
[0041] Example 2
[0042] A preparation method of a tellurium selenide molybdenum sulfide catalyst comprises the following steps: first, at 70°C, 1.5 mmol of selenium powder is added to 2.5 mL of hydrazine hydrate solution (98%) to form solution A. Then, 0.75 mmol of sodium molybdate dihydrate and 0.75 mmol of thiourea are dissolved in 10 mL of reduced graphene oxide suspension (10 mg / mL) to form a mixed solution B. Solution A and solution B are mixed together and stirred for 15 minutes to obtain solution C, and solution C is transferred to a Teflon autoclave and stored at 200°C for 24 hours. The product obtained by the reaction is washed with deionized water and freeze-dried to obtain a black product A. Finally, a tubular furnace is used for annealing treatment, 2 mmol of tellurium powder is placed in an upwind position, and product A is placed in a downwind position, and annealing treatment is performed at 600°C in an argon-hydrogen environment for 2 hours to obtain a tellurium selenide molybdenum sulfide catalyst.
[0043] Example 3
[0044] A preparation method of a tellurium selenide molybdenum sulfide catalyst comprises the following steps: first, at 70°C, 0.75 mmol of selenium powder is added to 2.5 mL of hydrazine hydrate solution (98%) to form solution A. Then, 0.75 mmol of sodium molybdate dihydrate and 1.5 mmol of thiourea are dissolved in 10 mL of reduced graphene oxide suspension (10 mg / mL) to form a mixed solution B. Solution A and solution B are mixed together and stirred for 15 minutes to obtain solution C, and solution C is transferred to a Teflon autoclave and stored at 200°C for 24 hours. The product obtained by the reaction is washed with deionized water and freeze-dried to obtain a black product A. Finally, a tubular furnace is used for annealing treatment, 5 mmol of tellurium powder is placed in an upwind position, and product A is placed in a downwind position, and annealing treatment is performed at 700°C in an argon hydrogen environment for 2 hours to obtain a tellurium selenide molybdenum sulfide catalyst.
[0045] Comparative Example 1
[0046] Preparation of molybdenum disulfide catalyst: Compared with the preparation in Example 1, solution A is not required, and the product obtained by hydrothermal treatment is annealed at 550° C. in a tubular furnace under the protection of argon, and the other steps remain the same to obtain a molybdenum disulfide catalyst.
[0047] Comparative Example 2
[0048] Preparation of molybdenum diselenide catalyst: Compared with the preparation in Example 1, no thiourea needs to be added to solution B, and the product obtained by hydrothermal treatment is annealed at 550° C. in a tubular furnace under the protection of argon, and the remaining steps remain the same to obtain a molybdenum diselenide catalyst.
[0049] Comparative Example 3
[0050] Preparation of molybdenum ditelluride catalyst: Compared with the preparation in Example 1, the selenium powder in solution A is replaced with tellurium powder of the same molar number, and thiourea is not required to be added to solution B. The product obtained by hydrothermal treatment is annealed at 550°C in a tubular furnace under the protection of argon, and the other steps remain the same to obtain a molybdenum ditelluride catalyst.
[0051] In order to evaluate the effectiveness of the MoSSeTe / rGO catalyst in actual lithium-sulfur batteries, sulfur was incorporated into the samples prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 by the conventional melt impregnation method to form a sulfur cathode and prepare a battery. The experimental steps are as follows: The synthesized molybdenum telluride selenide catalyst was combined with sulfur by grinding and then heated in an inert atmosphere at 155°C for 12h. Subsequently, the active material (70%), polyvinylidene fluoride (PVDF, 10%) and carbon black (20%) were dissolved in N-methylpyrrolidone (NMP) to prepare a slurry. The slurry was then coated on aluminum foil and dried in a vacuum oven at 60°C for 12h. The dried coated foil was cut into sheets with a diameter of 10mm. The cathodes synthesized in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 were S@MoS2 / rGO, S@MoSe2 / rGO, S@MoTe2 / rGO and S@MoSSeTe / rGO, respectively.
[0052] Figure 3 The performance diagram of the battery prepared with the catalysts obtained in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1. The cycle test was carried out under 1C conditions. The initial discharge capacity of the S@MoSSeTe / rGO-based battery prepared in Example 1 is 990 mAh·g -1 , exceeding the comparison S@MoTe2 / rGO-based battery (870mAh·g -1 , 74.6%), S@MoSe2 / rGO-based batteries (930mAh·g -1 ) and S@MoS2 / rGO-based batteries (835mAh·g -1 ) performance. This is due to the incorporation of selenium and tellurium, which expands the interlayer spacing and facilitates the rapid insertion / extraction of lithium ions. In addition, the excellent conductivity and catalytic effect on polysulfides significantly accelerate the redox reaction in lithium-sulfur batteries.
[0053] Therefore, the present invention adopts the above-mentioned preparation method and application of molybdenum tellurium selenide sulfide catalyst. The molybdenum tellurium selenide sulfide catalyst simultaneously introduces Se and Te, which are both chalcogen elements, into the MoS2 / rGO composite material, which will cause changes in the electronic structure of the catalyst, resulting in the upward shift of the d-band center and a decrease in the electron occupancy rate on the antibonding orbit. This modification effectively enhances the sulfur reduction reaction and significantly improves its conversion rate by changing the conversion pathway of polysulfides. In addition, this modification expands the interlayer spacing and promotes the rapid movement of lithium ions. The compound prepared by this method can be infinitely solid-dissolved and has a step-catalytic effect. The lithium-sulfur battery prepared using this catalyst as the positive electrode material has an initial capacity of 990mAh·g under 1C conditions. -1 , the capacity retention rate after 200 cycles is about 87%, showing great potential in lithium-sulfur batteries.
[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a molybdenum telluride selenide sulfide catalyst, characterized in that: The following steps are involved: S1, adding selenium powder to hydrazine hydrate solution to form solution A; S2, dissolving sodium molybdate dihydrate and thiourea in the reduced graphene oxide suspension to form a mixed solution B; S3, mixing solution A and solution B and stirring to obtain solution C, and placing solution C in an autoclave for hydrothermal reaction; S4, washing the product obtained by the hydrothermal reaction with deionized water, and freeze-drying to obtain a black product A; S5. Place the tellurium powder at the upwind side of the tubular furnace, and place the product A at the downwind side of the tubular furnace, and perform annealing treatment in an argon-hydrogen atmosphere to obtain a tellurium-selenium-molybdenum sulfide catalyst.
2. The method for preparing a molybdenum telluride selenide sulfide catalyst according to claim 1, characterized in that: The mixing temperature of selenium powder and hydrazine hydrate in S1 is 50-100°C, the purity of selenium powder is >99.99%, the particle size is <75μm, and the hydrazine hydrate is analytical grade.
3. The method for preparing a molybdenum telluride selenide sulfide catalyst according to claim 2, characterized in that: The purity of sodium molybdate dihydrate in S2 is >99.99%, and the concentration of reduced graphene oxide in solution B is 3-20 mg / mL.
4. The method for preparing a molybdenum telluride selenide sulfide catalyst according to claim 3, characterized in that: In S3, the stirring temperature is 40-80°C, the stirring time is 0.25-3h, the hydrothermal reaction temperature is 160-250°C, and the hydrothermal reaction time is 10-30h.
5. The method for preparing a molybdenum telluride selenide sulfide catalyst according to claim 4, characterized in that: The mass ratio of tellurium powder to product A in S5 is 1:2-0.1, the annealing temperature is 400-800°C, and the time is 1-6h.
6. The method for preparing a molybdenum telluride selenide sulfide catalyst according to claim 5, characterized in that: The concentrations of selenium powder, sodium molybdate dihydrate and thiourea in solution C are all 2-8 mmol / mL.
7. The method for preparing a molybdenum telluride selenide sulfide catalyst according to claim 6, characterized in that: The volume percentage content of hydrazine hydrate in solution C is 10-50%.
8. The method for preparing a molybdenum telluride selenide sulfide catalyst according to claim 7, characterized in that: The mass percentage of the single elements S, Se and Te in the molybdenum tellurium selenide sulfide catalyst is 10-80%.
9. An application of a tellurium selenide molybdenum sulfide catalyst, characterized in that: The molybdenum telluride selenide sulfide catalyst prepared by the method for preparing a molybdenum telluride selenide sulfide catalyst described in claim 8 is used as a positive electrode material in the preparation of a lithium-sulfur battery.
Citation Information
Patent Citations
Preparation method of g-C3N4 / MoS2 / ZnS nanocomposite
CN106241877A
Preparation method of thin-layer two-dimensional transition metal tellurium-based solid solution
CN110228796A
Transition metal and lean metal sulfur-selenium-tellurium composite material and preparation and application thereof
CN118867156A
Nanocomposite materials and methods for producing and using nanocomposite materials
US20220042186A1